Need assessment of the forcibly displaced Myanmar nationals - Shatil, Tanvir; Saha, Polin Kumar; Rahman, Atiya (BRAC Research and Evaluation Division, 2022)
There has been a continued influx of the Forcibly Displaced Myanmar Nationals (FDMN) across the border of Bangladesh and Myanmar since 25 August 2017. As a consequence, the large numbers of people (FDMN) have unexpectedly taken shelter in Bangladesh. Along with 307,500 Rohingya refugees now total 822, 500 FDMNs are living in various makeshift, unregistered and registered settlements of Cox’s Bazar in Bangladesh. So, it is realized that Bangladesh has been facing a severe challenge in providing food, shelter and protection assistance to these shelters. Till date, FDMN influx is underway and the new arrivals have little or no access to food, shelter, safe drinking water and healthcare. In response to the crisis, this study has been designed in aiming to reach standard humanitarian services to the FDMN people. Broadly, the assessment of the study is to understand the priority needs of the new arrivals and make a recommendation to mobilize resources and interventions. To observe and conduct the interviews of the targeted people, an assessment team has visited six makeshift camps of Cox’s Bazar district including, Unchiprang, Hakimpara, Kutupalong, Kutupalong extension, Balikhali 1, and Thankhali. Altogether, age and gender disaggregated 18 FGDs are conducted in seven days with more than 250 participants. In addition to FGD, the team conducts individual interviews with FDMN peoples and host communities. As an outcome of the study, the ongoing or prospective humanitarian responses have been resulted upon on the existing scenarios of fundamental needs (e.g. shelter, health, water, sanitation and hygiene (WASH), food, non-food items (NFI), and child protection) to the FDMN, including possible solution in relief distribution and strategic directions to overcome the challenges.